2019
DOI: 10.1021/acsomega.9b03098
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Acetate/P4VP-b-PEO Membranes for the Adsorption of Electron-Deficient Pharmaceutical Compounds

Abstract: The prevalence of pharmaceutical compounds in surface and groundwater presents a rising threat to human health. As such, the search for novel materials that serve to avoid their release into the environment or for the remediation once in the water effluent is of utmost importance. The present work describes the fabrication of a cellulose acetate membrane modified with the block copolymer poly(4-vinylpyridine-b-ethylene oxide) (P4VP-b-PEO) crafted for the specific targeting and adsorption of electron-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…It has been established that the PEO-b-P4VP is able to adsorb pharmaceutical compounds through electron donor−acceptor or π-π interactions. 21,22 Additionally, PEO-b-P4VP can interact with water molecules through hydrogen bonding, thus maintaining a hydrophilic character. Furthermore, the interaction between PEO and polyphenols has been widely studied and hydrogen bonds have been identified as the main mechanism of interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that the PEO-b-P4VP is able to adsorb pharmaceutical compounds through electron donor−acceptor or π-π interactions. 21,22 Additionally, PEO-b-P4VP can interact with water molecules through hydrogen bonding, thus maintaining a hydrophilic character. Furthermore, the interaction between PEO and polyphenols has been widely studied and hydrogen bonds have been identified as the main mechanism of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reported the interaction of the diblock copolymer (DiBCP) poly­(ethylene oxide- b -4-vinylpyridine) (PEO- b -P4VP) with different emerging contaminants present in water. It has been established that the PEO- b -P4VP is able to adsorb pharmaceutical compounds through electron donor–acceptor or π-π interactions. , Additionally, PEO- b -P4VP can interact with water molecules through hydrogen bonding, thus maintaining a hydrophilic character. Furthermore, the interaction between PEO and polyphenols has been widely studied and hydrogen bonds have been identified as the main mechanism of interaction. , Previous reports have proposed that the P4VP monomer on the block copolymer interacts with hydroxyl groups in surfaces, leaving PEO, the hydrophilic monomer, exposed and able to interact with the polyphenol through hydrogen bonding. , …”
Section: Introductionmentioning
confidence: 99%
“…The membranes obtained in this work are characterised by better adsorption properties and a higher permeability value than membranes made of Cellulose Acetate/P4VP-b-PEO and presented in [ 42 ]. Comparing the results of our paper with the results of papers [ 43 , 44 ] concerning the integrated ultrafiltration-photocatalysis process, it can be concluded that the degree of sulfadiazine removal is comparable for both methods with similar permeability values.…”
Section: Resultsmentioning
confidence: 99%
“…Laura et al fabricated a cellulose acetate-based membrane modified with block co-polymer poly(4-vinylpyridine- b -ethylene oxide) (P4VP- b -PEO) for the adsorption of several electron-deficient EDPs. 189 This study showed that the adsorption behavior of the membrane is directly relevant to the electron deficiency and spatial orientation of the contaminants. Moreover, the incorporation of 1% P4VP- b -PEO into the CA membrane significantly enhances the adsorption efficacy by at least 2-fold.…”
Section: Cellulose Acetate-based Membrane For Wastewater Treatmentmentioning
confidence: 87%
“…In case of CA-based membrane, negative functional groups such as hydroxyl and carboxylic groups are predominant, which can adsorb positively-charged pharmaceuticals. 189,190 Removal by the charge repulsion mechanism arises when the charge of the membrane surface and the ions of the electrolyte in pharmaceutical and personal care products (PPCPs) are similar and prevent the ion from contacting the membrane. 187 In the sieving mechanism, pollutants are separated by molecular size if molecules are larger than the membrane pores that cannot pass through the membrane.…”
Section: Cellulose Acetate-based Membrane For Wastewater Treatmentmentioning
confidence: 99%